Atom-Atom entanglement generation via collective states of atomic rings - Nadav Antman Ron; Maor Carmi; Rivka Bekenstein (Physical Review Research)
Subwavelength atomic lattices have been established as a promising platform for quantum applications, utilizing collective superradiant and subradiant behavior to enhance atom-light interactions. While previous work has demonstrated high-fidelity atom-photon entanglement in these systems, the generation of atom–atom entanglement, a crucial ingredient for full scalability, remains a conceptual challenge. Here, we propose methods for high-fidelity entanglement generation between atomic qubits by identifying specific atoms within a ring array as qubits. The entanglement generation is achieved by collective atomic excitation involving both subradiant and superradiant states and leveraging the novel symmetry properties of the ring array. Specifically, we utilize symmetry breaking within the ring by preparing atomic qubits in a superpositions of detunings for our entanglement protocols. A fidelity analysis of the protocols provides practical experimental parameters for state-of-the-art setups.